On the Molecular Origin of the Toxicity of Erophaca baetica (L.) Boiss. - Mounia Chroho; Latifa Bouissane; Christian Bailly (Future Pharmacology, 2025)
Background/Objectives: The plant species Erophaca baetica (L.) Boiss. (synonym: Astragalus lusitanicus Lam.) is found essentially around the Mediterranean basin, with Morocco as its ancestral territory. The foliage of E. baetica is toxic to small ruminants, and for this reason the plant is often eliminated by farmers, despite its ecological and medicinal potential. The phytochemicals at the origin of the toxicity of E. baetica are not precisely known, but several potentially toxic products have been identified. In particular, aliphatic nitro compounds are present in the aerial parts of the plant, such as 3-nitro-propionic acid (NPA) and its precursor 3-nitro-propanol (NPOH) which are most likely at the origin of the plant toxicity. Results: The present review provides a detailed analysis of the nitrotoxins isolated from E. baetica and their mechanism of action. The covalent targeting of metabolic enzymes such as isocitrate lyase and succinate dehydrogenase by NPA is discussed. The mitochondrial chain blocker NPA is most likely responsible for the brain toxicity of E. baetica, but the presence of other potentially toxic chemicals—such as lusitoxamine and lusitoxamide—is also discussed. Conclusions: This review shed light on the widespread but little-known Mediterranean plant E. baetica and the phytochemicals responsible for the plant’s toxicity.